The proportion of circulating gammadelta T cells increases after the first week of onset of tularaemia and remains elevated for more than a year - Kroca, M; Tärnvik, A; Sjöstedt, A (Clinical and experimental immunology, 2000)
In various human intracellular bacterial diseases, an increase of the proportion of circulating Vgamma9Vdelta2 T cells has been observed. The prevalence of the finding among infected subjects and the time course of the elevation remain to be investigated. In the present study, comprising blood samples from a large number of cases of ulceroglandular tularaemia, the percentage of Vgamma9Vdelta2 T cells within the first week of onset of disease (5.3 +/- 0.7% (mean +/- s.e.m.)) did not differ from that of control subjects (5.3 +/- 0. 8%). Thereafter, percentages increased rapidly and within the interval of 8-40 days mean levels were > 20% (P < 0.001). Of 45 individuals sampled within 3 months of onset, 42 showed a percentage of Vgamma9Vdelta2 T cells of > 10%. Significantly increased levels were still recorded at 18 months (13.8 +/- 2.4%; P < 0.05) but not at 24 months (10.2 +/- 2.1%; P > 0.10). Thus, a consistent increase of circulating Vgamma9Vdelta2 T cells was demonstrated in tularaemia. The initial delay and the prolonged course of elevation may suggest a role in immunoregulation and/or immunological memory. Furthermore, the percentage of gammadelta T cells expressing tumour necrosis factor-alpha in response to phorbol myristate acetate was decreased during the first week and up to 40 days after onset, possibly reflecting the modulation of an inflammatory response.